Online Learning amidst Global Pandemic: EFL Students’ Challenges, Suggestions, and Needed Materials - Nartiningrum, Novrika; Nugroho, Arif (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Covid-19 pandemic brings changes in many aspects of peoples’ lives throughout the world. The spread of Covid-19 in Indonesia affects the education system in this country. Face-to-face instructions are shifted into full online learnings from home. Despite this quite drastic change, the literature on students’ insights of this matter has still been silent. Thus, the present study elucidates 45 EFL students’ challenges, suggestions and needed materials during these online classes. Rely on qualitative data analysis from written responses and semi-structured interviews, the findings disclosed that these EFL students’ main challenges in attending online courses were the unsteady networks and the less direct interactions. These students mainly suggested the use of video conferencing applications such as zoom or Google meet, though some students chose assignments over those applications. The students also mentioned that they basically needed grammar related materials within the online classes. The findings bring forward the picture of full online learning condition during Covid-19 outbreak on EFL setting in Indonesia.